The Singing Teaching Techniques of Shanxi Folk Songs in China - Fei , Li; Pattananon, Nicha (Journal of Modern Learning Development, 2023)
Shanxi folk songs have their own strong and unique style because of their historical culture and geographical environment. Shanxi has been the province of choice for many dynasties to build cities since ancient times, such as the "Capital of Yao in Pingyang," "Capital of Shun in Puban," and "Capital of Yu in Anyi." Various musical instruments were found in unearthed cultural relics more than 4,000 years ago. Pottery Xun in Neolithic Age, stone chimes in Xia Dynasty, Yong bells in Spring and Autumn Period, and other objects indicate the blooming development of Shanxi’s art and culture. The article presents the singing teaching technique of Shanxi folk songs, which had a unique and particular style.